2015
DOI: 10.1111/codi.12905
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation for faecal incontinence and constipation: a European consensus statement

Abstract: Consensus was achieved on the majority of domains of SNS/SNM for FI and constipation. This should serve as a benchmark for safe and quality practice of SNS/SNM in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 149 publications
(172 reference statements)
1
67
0
4
Order By: Relevance
“…There is a large and growing body of evidence that a defect of the internal or external sphincter is not a contraindication for SNM for FI . Though clinical success has been reported in patients with sphincter defects up to 180 degrees, most would agree that the size of the defect does not matter and should not affect decision making .…”
Section: Fecal Incontinence (Fi)mentioning
confidence: 99%
“…There is a large and growing body of evidence that a defect of the internal or external sphincter is not a contraindication for SNM for FI . Though clinical success has been reported in patients with sphincter defects up to 180 degrees, most would agree that the size of the defect does not matter and should not affect decision making .…”
Section: Fecal Incontinence (Fi)mentioning
confidence: 99%
“…These findings may indicate that severe concomitant urinary incontinence is a predictor of successful outcome after SNM for combined faecal and urinary incontinence. The absence of evidence makes this hypothesis difficult to substantiate [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The patient should have slow transit constipation and/or symptoms of outlet obstruction without a mechanically correctable cause". 34 Studies have shown improvement in objective outcomes after SNM using anorectal physiology, defecography and or transit times. 35 Ganio et al found increased maximum squeeze pressure as well as a reduction in the volume needed for urge sensation (p<0.01).…”
Section: Constipationmentioning
confidence: 99%